THE EFFECT OF REWARD PROVISION ON TAXPAYERS (Individual Taxpayers in the Notary Profession in Indonesia) - Muhammad Kurniawan Al Bashir Tamar; Herlin Tundjung Setijaningsih (PT. Radja Intercontinental Publishing, 2025)
Tax compliance plays a crucial role in maximizing state income; nonetheless, the level of compliance among individual taxpayers in Indonesia is still quite low. Offering incentives is viewed as one of the techniques that can boost taxpayers' enthusiasm and understanding in meeting their tax responsibilities. This research intends to investigate how the provision of incentives impacts the tax compliance of individual taxpayers, particularly notaries in Indonesia. The study utilizes a quantitative method with a survey approach, collecting notary responses through Google Forms. Information was gathered via a questionnaire that had been validated for accuracy and consistency. The analysis of the data was performed using simple linear regression to evaluate how the reward variable affects the tax compliance level. The findings suggest that the provision of incentives positively and significantly influences the tax compliance of notary taxpayers.